Theoretical investigation on a simple turn on fluorescent probe for detection of biothiols based on coumarin unit - Ma, Tianhao; Huang, He; Liu, Yuling; Peng, Yongjin (Frontiers in Chemistry, 2023)
It is scientific significant for exploitation of a simple and efficient detection method on the biothiols due to the crucial role of them in various physiological processes. Recently a simple fluorescent probe DEMCA-NBSC based on coumarin fragment was developed by Ding et al, which provided an efficient way for real-time sensing the biothiols both in vivo and vitro. Theoretical insights of the fluorescence sensing mechanism of the probe were provided in this work. The detail of the electron transfer process in the probe under optical excitation and the fluorescent character of the probe were analyzed using quantum mechanical method. All these theoretical results could be inspiring for developing highly convenient and efficient fluorescent probe to sense the biothiols both in vivo and vitro.